Development of Immunological Assays Based on Leishmania donovani Antigen for Diagnosis of Canine Visceral Leishmaniasis and Their Multicenter Evaluation in Brazil and Italy - Ejazi, Sarfaraz Ahmad; Saha, Samiran; Bhattacharyya, Anirban; Das, Sonali; Mateus, Nathália Lopes Fontoura; da Costa Lima, Manoel Sebastião; Neitzke-Abreu, Herintha Coeto; de Mendonca, Ivete Lopes; Costa, Carlos Henrique Nery; de Oliveira Melo, Otoni Alves; de Melo, Marcia Almeida; Rossi-Bergmann, Bartira; et al. (Frontiers in Cellular and Infection Microbiology, 2022)
Canine visceral leishmaniasis (CVL) due to Leishmania infantum infection is a zoonotic disease prevalent in the areas of South America and the Mediterranean. Infected dogs as reservoirs can contribute to disease transmission and can be a scourge to public health. Therefore, early diagnosis of infected dogs may play a pivotal role in circumscribing disease progression. Invasive tissue aspiration and insufficient serological methods impair a single assay for prompt CVL diagnosis. In the present study, we aimed to evaluate the potential of Leishmania donovani isolated membrane protein, LAg, for the diagnosis of CVL through immunological assays. Initially, ELISA was done with Brazilian dog sera to evaluate the performance of LAg in diagnosing CVL and found sensitivity and specificity of 92.50% and 95%, respectively. The study further confirmed the diagnostic efficacy of LAg in a dipstick format. The dipstick test of canine sera from three centers in Brazil and one center in Italy collectively showed sensitivity values in the range of 53.33% to 100% in recognizing symptomatic dogs and specificity values between 75% and 100% to rule out healthy dogs. Moreover, a rapid immunochromatographic test was developed and optimized using LAg. ICT was able to identify 94.73% of CVL of Brazilian origin with 97.29% specificity. The current results highlight the reactive potential of the L. donovani antigen, LAg, for L. infantum CVL diagnosis and support our previous findings which suggest the utility of LAg for the diagnosis of both L. donovani and L. infantum human VL in a variety of endemic regions. LAg as a diagnostic candidate may be employed to identify comprehensive CVL cases in epidemiological areas.